PPARγ-p53-Mediated Vasculoregenerative Program to Reverse Pulmonary Hypertension. Issue 3 (5th February 2021) - Hennigs, Jan K.; Cao, Aiqin; Li, Caiyun G.; Shi, Minyi; Mienert, Julia; Miyagawa, Kazuya; Körbelin, Jakob; Marciano, David P.; Chen, Pin-I; Roughley, Matthew; Elliott, Matthew V.; Harper, Rebecca L.; et al.
Abstract : Rationale: In pulmonary arterial hypertension (PAH), endothelial dysfunction and obliterative vascular disease are associated with DNA damage and impaired signaling of BMPR2 (bone morphogenetic protein type 2 receptor) via two downstream transcription factors, PPARγ (peroxisome proliferator-activated receptor gamma), and p53. Objective: We investigated the vasculoprotective and regenerative potential of a newly identified PPARγ-p53 transcription factor complex in the pulmonary endothelium. Methods and Results: In this study, we identified a pharmacologically inducible vasculoprotective mechanism in pulmonary arterial and lung MV (microvascular) endothelial cells in response to DNA damage and oxidant stress regulated in part by a BMPR2 dependent transcription factor complex between PPARγ and p53. Chromatin immunoprecipitation sequencing and RNA-sequencing established an inducible PPARγ-p53 mediated regenerative program regulating 19 genes involved in lung endothelial cell survival, angiogenesis and DNA repair including, EPHA2 ( ephrin type-A receptor 2 ), FHL2 ( four and a half LIM domains protein 2 ), JAG1 ( jagged 1 ), SULF2 ( extracellular sulfatase Sulf-2 ), and TIGAR ( TP53-inducible glycolysis and apoptosis regulator ). Expression of these genes was partially impaired when the PPARγ-p53 complex was pharmacologically disrupted or when BMPR2 was reduced in pulmonary artery endothelial cells (PAECs) subjected to oxidative stress. In endothelial cell-specific Bmpr2 -knockout mice unable to stabilize p53 in endothelial cells under oxidative stress, Nutlin-3 rescued endothelial p53 and PPARγ-p53 complex formation and induced target genes, such as APLN ( apelin ) and JAG1, to regenerate pulmonary microvessels and reverse pulmonary hypertension. In PAECs from BMPR2 mutant PAH patients, pharmacological induction of p53 and PPARγ-p53 genes repaired damaged DNA utilizing genes from the nucleotide excision repair pathway without provoking PAEC apoptosis. Conclusions: We identified a novel therapeutic strategy that activates a vasculoprotective gene regulation program in PAECs downstream of dysfunctional BMPR2 to rehabilitate PAH PAECs, regenerate pulmonary microvessels, and reverse disease. Our studies pave the way for p53-based vasculoregenerative therapies for PAH by extending the therapeutic focus to PAEC dysfunction and to DNA damage associated with PAH progression. Abstract : Supplemental Digital Content is available in the text.